Edukasi Literasi Emosi Sebagai Upaya Pencegahan Perundungan pada Siswa Sekolah Menengah Pertama - Hastutis, Rahmah; Lysander, Celina; Florenxia, Kharine (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescence is a developmental stage marked by significant physical, cognitive, and socio-emotional changes that may increase vulnerability to psychosocial problems, including difficulties in emotion regulation and bullying behavior. This Community Service Program (Pengabdian Kepada Masyarakat/PKM) aimed to enhance emotional literacy and anti-bullying awareness among students of SMP Atisa Dipamkara, Tangerang. The program was conducted through an interactive psychoeducational seminar discussing emotion recognition, adaptive emotion regulation strategies, and forms and impacts of bullying in the school environment. Evaluation was carried out using emotion regulation and bullying questionnaires to obtain an overview of students’ conditions after the activity. The results indicated an improvement in students’ understanding of the importance of managing emotions and promoting mutual respect, although verbal bullying was still reported. Overall, this program contributes to school-based preventive efforts and is recommended to be implemented continuously with the support of teachers and parents.